Potensi Cynara Scolymus (Artichoke) Pengobatan Herbal Obesitas - Riska Putri Soraya Putri Soraya (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Obesity is a condition that occurs due to higher energy intake than that spent or excessive food consumption without any meaningful physical activity. Lifestyle influences one's eating habits and impacts on nutrition. Obesity becomes the new world syndrome because the number of events continues to increase. The achievement of the Human Development Index in the world is inseparable in terms of improving the quality of health. However, currently, there are still many nutritional problems that affect the quality of health. Obesity is not just a health problem, but a matter of awareness. So that therapy is needed to reduce the incidence of iron. Herbal plants are currently being used for obesity. C. Scolymus is an herbal plant that has anti-obesity potential by inhibiting digestive enzymes (pancreatic lipase, α-amylase, α-glucosidase), effects of bile secretion, inflammation, and ROS, increasing liver enzymes, increasing lipolysis and lipid metabolism, increasing intestinal microbiota, and reducing blood glucose can be obese patients